2012
DOI: 10.1212/wnl.0b013e31826846b4
|View full text |Cite
|
Sign up to set email alerts
|

The earlier, the smaller, the better for natalizumab-associated PML: In MRI vigilance veritas?

Abstract: THE EARLIER, THE SMALLER, THE BETTER FOR NATALIZUMAB-ASSOCIATED PML: IN MRI VIGILANCE VERITAS?Natalizumab-associated progressive multifocal leukoencephalopathy (N-PML) in multiple sclerosis (MS) is due to CNS infection by the opportunistic JC virus (JCV). As of December 2011, 193 confirmed cases of N-PML have been observed, giving rise to an overall risk of approximately 0.202%. 1 N-PML pathogenesis remains partially elusive although risk factors have now been clearly delineated.2 In patients with prior JCV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
(11 reference statements)
3
21
0
Order By: Relevance
“…The three deaths occurred indeed in patients with symptomatic PML and higher numbers of CSF-DNA viral copies at PML diagnosis. This is in line with previously published data on predictors of survival and functional outcomes [1618] and indicates that the later the PML diagnosis was made, the more the disease was widespread. Therefore, our study strongly supports the deferral of further NTZ dosing until exclusion of PML diagnosis in case of unexpected clinical worsening or new MRI lesions occurring beyond the first year of therapy [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The three deaths occurred indeed in patients with symptomatic PML and higher numbers of CSF-DNA viral copies at PML diagnosis. This is in line with previously published data on predictors of survival and functional outcomes [1618] and indicates that the later the PML diagnosis was made, the more the disease was widespread. Therefore, our study strongly supports the deferral of further NTZ dosing until exclusion of PML diagnosis in case of unexpected clinical worsening or new MRI lesions occurring beyond the first year of therapy [39].…”
Section: Discussionsupporting
confidence: 92%
“…Some clinical and paraclinical features at NTZ-related PML diagnosis have been reported to be predictive of bad outcome, including older age, high pre-PML disability, MRI findings consistent with multifocal damage, elevated number of JCV copies detected in cerebrospinal fluid (CSF) and symptomatic PML [1618]. However, literature data regarding clinical outcomes after PML suffer from several biases, including incomplete data collection, largely heterogeneous management of patients and not univocal definition of PML-IRIS [15, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, European centers may have been performing MRI scans more frequently, as suggested in a PML case report published in 2012 in which the authors described performing brain MRI scans every 6 months for all relapsing MS patients treated with natalizumab 38. The PML case reported by Phan-Ba and colleagues was also included in a case series, in which a group of European authors suggested that “brain MRI scans every 3–4 months could be considered for interval MRI vigilance.”24 Similarly, in a set of recommendations published in 2011 by the International Multiple Sclerosis Expert Forum, it was stated that “more frequent MRI has been suggested (every 3–6 months)” in patients at increased risk for PML 12. Although our data were limited, no clear pattern of frequency of MRI testing was discerned between those patients who were asymptomatic and those who were symptomatic.…”
Section: Discussionmentioning
confidence: 66%
“…In the context of opportunistic infections, the current data and a number of recent case reports17,18,21,23,24 suggest that PML may be diagnosed based on brain MRI findings and the presence of JCV DNA in the CSF or on brain biopsy in the absence of clinical symptoms. This observation departs from the traditional 3-part diagnostic algorithm requiring clinical symptoms in combination with MRI findings and JCV DNA detection in the CNS for a diagnosis of definite PML 10,35,36.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation